Influence of Nd:YAG Laser Energy on Mechanical properties of Nitriding Steel - Aziz, Ansam Abdul Jabbar; Khalid, Enass A.; Alwan, Abbas S. (Al-Nahrain Journal for Engineering Sciences, 2020)
Desired mechanical properties like microstructure, micro hardness and wear resistance are the key parameters for which low carbon steel (AISI 1006) are widely selected. Surface heat treatment applied to improve these properties; traditionally surface heat treatments like induction hardening, in recent time’s laser surface hardening. In this work, thermochemical treatment (liquid nitriding) by using mixture from 61% NaCN, 15% K2CO3 and 24% KCL and followed by Nd:YAG laser surface treatment was done . The laser parameter were energy (0.89, 2, 4 and 9) J, spot diameter (0.790 ,0.33, 0.283 and 0.224) mm, pulses duration (1, 2.33, 4.47 and 9.87) ms with  fix wavelength 1604nm. Laser surface treatment cycle was melting the layer surface, holding and rapid cooling in air medium.  Optical microscopy (OM) and scanning electron microscope (SEM) has been used to study the microstructures and cross-sectional of molted and heat affected zones respectively. The wear test was done to measure the wear rate by using pin -on-disk principles were satisfied. The result shown that increasing in laser energy effects to increase in the area of melted and heat affected zones of nitriding steel. Also increasing in laser energy led to increase micro hardness about 61%, while wear rate decrease about 40 % and increased depth of molted zone.